PENGARUH LATIHAN INTERVAL TERHADAP PENINGKATAN KAPASITAS VO2 MAKS PEMAIN AKADEMI AREMA FC U16 - Muhammad Sholihin Efendy; Olivia Andiana; Heri Purnama Pribadi (KORSA: Jurnal Kajian Ilmu Keolahragaan dan Kesehatan, 2023)
Football demands good aerobic endurance, or VO2 max, because it is one of the dominant sports using the aerobic energy system. Soccer players can increase their VO2 max capacity through interval training. The AREMA FC U16 Academy does not yet have a specific training program to increase VO2 max capacity. The purpose of this study was to determine the increase in VO2 max capacity after being given interval training by AREMA FC academy players. The research was conducted in the field of the National Institute of Technology (ITN) campus 2 using a quantitative research type with an experimental method (one group pretest-posttest design). The design aims to allow the research results to be known more accurately both before and after treatment. The research sample consisted of 25 AREMA FC academy players, aged between 14 and 16 years, who were male. The interval training program is given three times a week for six weeks. The research instrument used the bleep test to assess the maximum oxygen consumption (VO2 max) before and after being given treatment. The paired samples t test resulted in a significance value of 0.00<0.05. So it can be concluded that interval training has a positive impact on increasing VO2 max in AREMA FC U16 Academy players.